2011
DOI: 10.1177/0731684411412643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-profile additives on thermo-mechanical properties of glass fiber-reinforced unsaturated polyester composites

Abstract: Low profile additives (LPA) are thermoplastics particles incorporated into unsaturated polyester (UP) resin in order to improve the surface finish of fiber glass/UP composites by shrinkage compensation. They are widely used in automotive applications where high-quality surface finish is required. In this article, the effect of low-profile additives on the thermomechanical properties of resin transfer molded fiber glass/UP panels is investigated. A combination of poly vinyl-acetate and poly methyl-methacrylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…One study has shown that polyethylene glycol dimethacrylate networks modified by the addition of pre-polymerized beads of polymethyl methacrylate show significantly less shrinkage than it would have been predicted [74]. The same results have been reported for polyesters [31,32] and polystyrene modified by urethanes [37][38][39][40]. In some cases, the mechanism for shrinkage reduction has been correlated with void formation at the domain interface, which reduces the net dimensional change [74].…”
Section: Reaction Kinetics In Polymerization-induced Phase-separationsupporting
confidence: 60%
See 1 more Smart Citation
“…One study has shown that polyethylene glycol dimethacrylate networks modified by the addition of pre-polymerized beads of polymethyl methacrylate show significantly less shrinkage than it would have been predicted [74]. The same results have been reported for polyesters [31,32] and polystyrene modified by urethanes [37][38][39][40]. In some cases, the mechanism for shrinkage reduction has been correlated with void formation at the domain interface, which reduces the net dimensional change [74].…”
Section: Reaction Kinetics In Polymerization-induced Phase-separationsupporting
confidence: 60%
“…For example, in many applications, the control of polymerization shrinkage is crucial to the quality and longevity of the polymeric structure, such as in the molded parts and coatings industries, in electronics, and in biomedical fields. One approach that has been used for several years is the induction of phase separation by the addition of pre-polymerized additives [31,32,[72][73][74]. One study has shown that polyethylene glycol dimethacrylate networks modified by the addition of pre-polymerized beads of polymethyl methacrylate show significantly less shrinkage than it would have been predicted [74].…”
Section: Reaction Kinetics In Polymerization-induced Phase-separationmentioning
confidence: 99%
“…All the cured UPR specimens were prepared according to ISO 3672‐2:2000 as well as the references, and the formulation was set as 100 g resin : 1 g initiator : 0.5 g promoter. The mass ratio of LSA used in production is usually more than 30 g per 100 g UPR . In the experiment, the additions of LSAs were set at 5 g, 10 g, 15 g, 20 g, 25 g, and 30 g to control the content of LSAs within 30 g per 100 g UPR and to weaken the influences of LSAs on the properties of cured UPR.…”
Section: Methodsmentioning
confidence: 99%
“…These are polyvinyl acetate, polyurethane (PU), PMMA, polystyrene, and plasticizers. 34 Polystyrene is one of the most common materials used in tensile additives.…”
Section: Methodsmentioning
confidence: 99%